Hydrothermal Galvanic-Replacement-Tethered Synthesis of Ir-Ag-IrO2 Nanoplates for Computed Tomography-Guided Multiwavelength Potent Thermodynamic Cancer Therapy - Yim, Gyeonghye; Kang, Seounghun; Kim, Young-Jin; Kim, Young-Kwan; Min, Dal-Hee; Jang, Hongje (AMER CHEMICAL SOC, 2019)
Beyond the synthesis of typical nanocrystals, various breakthrough approaches have been developed to provide more useful structural features and functionalities. Among them, galvanic replacement, a structural transformation reaction accompanied by constituent element substitution, has been applied to various areas. However, the innovative improvement for galvanic replacement needs to be considered because of the limitation of applicable element pairs to maintain structural stability. To expand the boundary of galvanic-replacement-mediated synthesis, we have become interested in the Group 9 metallic element Ir, which is considered a fascinating element in the field of catalysis, but whose size and shape regulation has been conventionally regarded as difficult. To overcome the current limitations, we developed a hydrothermal galvanic-replacement-tethered synthetic route to prepare Ir-Ag-IrO2 nanoplates (IrNPs) with a transverse length of tens of nanometers and a rough surface morphology. A very interesting photoreactivity was observed from the prepared IrNPs, with Ag and IrO2 coexisting partially, which showed photothermal conversion and photocatalytic activity at different ratios against extinction wavelengths of 473, 660, and 808 nm. The present IrNP platform showed excellent photothermal conversion efficiency under near-infrared laser irradiation at 808 nm and also represented an effective cancer treatment in vitro and in vivo through a synergistic effect with reactive oxygen species (ROS) generation. In addition, computed tomography (CT) imaging contrast effects from Ir and IrO2 composition were also clearly observed.
Keywords: GOLD NANOPARTICLES; DRUG-DELIVERY; IRIDIUM; RESISTANCE; OXIDATION; DIAGNOSIS; RESONANCE; NANODOTS; INSIGHTS